The Effect of Health Insurance on the Utilization of Health Services: A Systematic Review and Meta-Analysis: - Shami, Elham; Tabrizi, Jafar Sadegh; Nosratnejad, Shirin (Galen Medical Journal, 2019)
Insurance organizations are among the most influential organizations in the health system, which can lead to healthcare efficiency and patient satisfaction in case they are increasingly accessed. The main purpose of the present systematic review was to examine the effect of health insurance on the utilization of health services and also to examine the factors affecting it. The present study was a systematic review that aimed to examine the effect of health insurance on the utilization of health care services. The study was conducted in 2016 using Scopus, PubMed, Web of Science, Science Direct, and ProQuest databases. We examined the utilization rate of health insurance in insured people. The inclusion and exclusion criteria were included based on review and meta-analysis purposes. The utilization of health services increased for inpatient and outpatient services. The utilization rate of inpatient services increased by 0.51% whereas the utilization rate of outpatient services increased by 1.26%. We classified the variables affecting the utilization rate of insurance into three main categories and sub-categories: demographic variables of the household, socioeconomic status, and health status. Our study showed that insured people increased the utilization rate of health services, depending on the type of health services. Thus, health policymakers should consider the community’s health insurance as a priority for health programs. For now, implementing universal health insurance is a good solution. [GMJ.2019;8:e1411]